New data on the many-plumed moths (Alucitidae, Lepidoptera) of the Far East of Russia - Petr Ustjuzhanin; Vasily Kovtunovich (Nota Lepidopterologica, 2014)
Orneodes zonodactyla var. eumorphodactyla Caradja, 1920 is regarded as a valid species with the following combination: Pterotopteryx eumorphodactyla (Caradja, 1920), comb.nov. Alucita sakhalinica Zagulajev, 1995 and Pterotopteryx koreana Bong-Kyu Byun, 2006, are synonymized with Pterotopteryx eumorphodactyla (Caradja, 1920). New data on the distribution of P. eumorphodactyla and Alucita ussurica Ustjuzhanin, 1999 in the Russian Far East are given.